Pengaruh Faktor Produksi terhadap Produksi Usahatani Padi Sawah di Desa Sanggi-Sanggi Kecamatan Palangga Kabupaten Konawe Selatan - Hartina, Hartina; Tuwo, Muhammad Akib; Indarsyih, Yusna (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2018)
This study aims to determine the factors of production that significantly affect the production of rice farming, consisting of two factors, namely land and experience of farmers in farming in the real level of 95%. While factors of production such as seed, fertilizer, labor, and education have no effect on the real significance of the set. Village studio Studio District Palangga Sub-district of Kabupaten Konawe South. The population was 55 as respondents. Determining the sample done by simple random sampling. Analysis of the data used is analysis Cob Douglas. The results showed that the respondents receiving an average of Rp25,541,818. Once it is recognized revenue of Rp. 19,497,227.